Activity evaluation on Ribes species, traditionally used to speed up healing of wounds: With special focus on Ribes nigrum - Kendir, Gulsen; Suntar, Ipek; Ceribasi, Ali Osman; Koroglu, Aysegul (Elsevier Ireland Ltd, 2019)
Ethnopharmacological relevance: Ribes species are usually evergreen shrubs, represented by eight species in Turkey. Although they are known for their fruits with commercial importance, their leaves have been used as folk remedy in various areas in Turkey by rural population owing to their wound healing potential. Aim of the study: In the present study we aimed to assess the wound healing activity of the leaves of Ribes species growing in Turkey, namely, Ribes alpinum L., R. anatolica Behcet, R. petraeum Wulfen, R. multiflorum Kit. ex Romer & Schultes, R. nigrum L, R. orientale Desf., R. rubrum L, R. uva-crispa L. Materials and methods: Wounds were surgically induced on the dorsal parts of the rats and mice. Prepared herbal ointments were topically applied onto the wounds once daily. The effects of the extracts were evaluated by measuring the breaking strength and percentage of reduction in wounded area by comparing the results with the registered reference ointment, FITO Krem (R). Histopathological and antioxidant assays were also conducted. Since, R. nigrum was determined to be the most active species, we further investigated the wound healing potential of the subextracts of the methanol extract of R. nigrum leaves. Results: R. nigrum and R. multiflorum extracts significantly increased wound breaking strength. Significant reduction in the areas was determined for the wounded tissues treated with the ointments of R. nigrum and R. multiflorum extracts. Oxidative Stress Index was found to be lowest for R. orientale, R. nigrum and R. multiflorum. Among the subextracts of R. nigrum, ethyl acetate subextract was found to have promising effect. Conclusions: Methanol extracts of leaves of R. nigrum and R. multiflorum demonstrated significant wound healing effect. We can suggest that ethyl acetate subextract of R. nigrum may be a potential candidate to be used for the development of a wound healing agent.
Keywords: Excision; Breaking strength; Grossulariaceae; Incision; Ribes nigrum; Wound healing